A Systematic Literature Review on the Circular Economy and Sustainability - Hetami, Adietya Arie (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study focuses on the significant shift from a linear to a circular economy, a topic that has recently gained traction in both business and academic sectors. Despite being a relatively new concept, the circular economy and its associated business models are garnering increased attention, necessitating the development of tools to aid their implementation. The aim of this study is to systematically explore the growing research interest in the circular economy and sustainability. The study employs a qualitative approach, conducting a comprehensive review of literature across various domains where the circular economy is applicable. These include sustainability, consumer behavior, innovation, remanufacturing, operations management, supply chains, intellectual capital, 3D printing, big data, and recycling. The study also delves into its relationship with small to medium-sized enterprises, and its impact on specific sectors like textiles and food. The goal is to pave the way for a sustainable solution that challenges the current linear model of production and resource management. Despite its novelty, the circular economy holds the promise of fostering positive synergies across economic, social, and environmental spheres.